IMPLEMENTATION OF THE MOVEMENT TO STRENGTHEN RELIGIOUS OPEN-MINDEDNESS AT THE MINISTRY OF RELIGION OF KEDIRI CITY IN 2024 - Siti Mahmudah; Siti Aminah; Eka Yuni Wulandari (RADJA PUBLIKA, 2025)
Religious open-mindedness is the mindset, outlook, and conduct of religious individuals in carrying out their faith in a proper and appropriate manner—that is, without being radical or extremist. In order to practice religion in moderation, we need to be tolerant and nonviolent. Since Religious open-mindedness is under the Ministry of Religion's jurisdiction, all of the Ministries of The religion's organizational tools and human resources need to be fully aware of its objectives. The goal of this study is to determine how the Kediri City Ministry of Religion can execute the movement to improve Religious open-mindedness. The research methodology is descriptive and qualitative. methods for gathering data through documentation, observations, and interviews. According to research findings, the Ministry of Religion in Kediri City has successfully implemented the movement to strengthen Religious open-mindedness. Among the activities that have been carried out are the creation of Religious open-mindedness villages, religious workshops for the development of Religious open-mindedness villages, pioneer orientation activities for the movement to strengthen Religious open-mindedness, discussions on Religious open-mindedness, and the provision of operational assistance for the development of Religious open-mindedness villages. The Ministry of Religion's efforts still require improvement through cooperation from other parties in order for this moderation movement to reach the lower classes and residents of Kediri City as a whole.